Pelanggaran Peraturan Perundang-Undangan di Bidang Pasar Modal yang Dilakukan oleh PT Sinergi Millenium Sekuritas - Ahmad Biky (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Capital markets become one of the important instruments for improving the economic wheel because it can help public companies or the government get financing or financing, but on the other hand opens opportunities for the community to be able to invest and increase its capital (capital gain) and profit or reward results (return). .One of the types of transactions that happens in the stock market is a REPO transaction (Repurchase Agreement) which are contract transactions or purchase effects with purchase or resale at the specified time and price. But the problem of this transaction still raises problems from some market players who violate the regulations in the field of capital markets that ultimately harm investors or customers as happened in the case PT Sinergi Millenium Sekuritas (PT SMS) in running REPO transactions carried out between Michael widja against 14 (fourteen) parties did not include an equity attachment and agency attachment in the agreement. Next, PT SMS did not have directors and/or employees authorized to conduct REPO transaction, where the director PT SMS should have authority in this is in accordance with existing regulations regarding REPO transactions. Things can also impact the decline in public confidence to invest his money in the capital market.